2014
DOI: 10.1095/biolreprod.114.119768
|View full text |Cite
|
Sign up to set email alerts
|

Acrosome Reaction and Ca2+ Imaging in Single Human Spermatozoa: New Regulatory Roles of [Ca2+]i1

Abstract: The spermatozoa acrosome reaction (AR) is essential for mammalian fertilization. Few methods allow visualization of AR in real time together with Ca²⁺ imaging. Here, we show that FM4-64, a fluorescent dye used to follow exocytosis, reliably reports AR progression induced by ionomycin and progesterone in human spermatozoa. FM4-64 clearly delimits the spermatozoa contour and reports morphological cell changes before, during, and after AR. This strategy unveiled the formation of moving tubular appendages, emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 43 publications
7
68
0
1
Order By: Relevance
“…A recent report has shown that stimulation of AR by progesterone in mouse sperm is absolutely dependent on a specific P4-induced transitory increase in [Ca 2+ ]i [37]. Moreover, alterations of the P4-induced [Ca 2+ ]i signal prevent the AR in human spermatozoa [38]. Thus, to investigate further the role of veratridine on AR, we evaluated its effect on the [Ca 2+ ]i response to P4.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report has shown that stimulation of AR by progesterone in mouse sperm is absolutely dependent on a specific P4-induced transitory increase in [Ca 2+ ]i [37]. Moreover, alterations of the P4-induced [Ca 2+ ]i signal prevent the AR in human spermatozoa [38]. Thus, to investigate further the role of veratridine on AR, we evaluated its effect on the [Ca 2+ ]i response to P4.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the presence of veratridine, the duration of the P4-induced [Ca 2+ ]i transient was increased, leading to a retard in the time to peak, and the phase of decay of the [Ca 2+ ]i transient was delayed. The broader [Ca 2+ ]i signal produced by P4 in the presence of veratridine might reflect a deregulation of the sperm Na + /Ca 2+ balance [39,40] and could avoid the presence of the second [Ca 2+ ]i peak to P4, necessary for the initiation of the AR, which is a tightly regulated mechanism [3,37,38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Progesterone is also known to stimulate several sperm functions, including hyperactivation 5 and acrosome reaction. 6 Hyperactivated motility might assist the sperm in penetrating the ZP, which is a critical process for fertilization. 7 Thus, we conclude that sperm motility becomes more vigorous in TFF/PFF patients, and sperm hyperactivation induced by progesterone is unlikely to induce TFF/PFF.…”
Section: Discussionmentioning
confidence: 99%
“…With the application of scanning electron microscopy (SEM) in reproductive medicine, the evaluation of human sperm ultrastructural morphology (SUM) has greatly increased. The SEM enables to observe and interpret the surface morphology of a human spermatozoon more easily and completely than with conventional light microscopy (Chemes, ; Moretti, Pascarelli, Belmonte, Renieri, & Collodel, ; Nussdorfer, Cilenšek, Zorn, & Petrovič, ; Ricci et al., ; Sánchez‐Cárdenas et al., ). Thus, examination of SUM using SEM can provide a useful additional approach to identify the status of SUM and aid a better understanding for certain etiologies of male infertility or fertilising failure.…”
Section: Introductionmentioning
confidence: 99%